The Accounting for Inventory from a Commercial Point of View - Dewi Purnamasari; Ayu Almira; Nadia Della Savira (Publindo Akademika, 2021)
Inventory control is a very important managerial function because the physical inventory of many companies involves the largest investment in current assets. The main purpose of inventory accounting is to determine periodic profit and loss through the process of bringing together the cost of goods sold with the sales proceeds in one accounting period and determining the amount of inventory to be presented in the balance sheet. This paper aims to describe the accounting for inventory from a commercial point of view. The method used in this study is qualitative in nature with a descriptive approach. The results showed that the main functions of inventory are to avoid delays in goods, loss of goods and with the presence of inventory, the company's operations can continue to run so that services to consumers can be carried out as well as possible. More specifically, the main functions of inventory are the decoupling function, economic lot-sizing function, and anticipation function. As the inventories become subject to regulations in Indonesia, the study also highlights the purposes of calculating the income tax of inventories. Article 10 paragraph (6) of the Income Tax Law states that inventories must be valued at cost. Therefore, if the taxpayer makes an assessment based on a method other than cost, an adjustment is required.